The Relation between Availability of New Collections and Users Motivation to Read: Correlation Study at the Library Unit of the Governance Institute of Home Affairs Jatinangor - Sardi, Auliya Noviyani (Indonesian Journal of Librarianship, 2021)
Background: Library as information providers needs to expand their collections in order to maintain the novelty of information used by users. The Library Unit of IPDN carries out collection development in the form of print and digital copy every year, but due to the limited space of ​​the library, new collections cannot be displayed and stored back in the warehouse after processing, so that new information takes longer to be obtained by the users even though there are more new printed collections available than the digital ones. Purpose: To find the relationship between the availability of new collections and users’ reading motivation. Method: This study uses quantitative methods with probability sampling technique, namely simple random sampling. The calculation is conducted by using Slovin formula with an error rate of 5% so as to produce 249 respondents. All instruments are declared valid based on the calculation of the Pearson Product Moment formula using a significance value of 5%. It is also declared reliable based on the calculation of the Cronbach Alpha formula. Meanwhile, the correlation test is conducted by using the Spearman-Rank formula. Result: The study shows several findings, such as: a) the new collection has an important value for the users with a score of 0.384 and is in the low proximity level; b) new collection relates to information enlargement. The result shows that it is in the medium proximity level with a value of 0.441; c) the relationship between the use of new collections and the expectations of collection development is in the medium category with a coefficient of 0.428; d) the relationship between the availability of new collections and reading motivation has a coefficient value of 0.513 and has a moderate proximity level. Conclusion: New collections can increase users’ knowledge thus the collections are valuable. When users’ information needs are fulfilled, users will have more expectations towards the collection development of the library. Therefore, the availability of new collections is related to users’ reading motivation. Keywords: Reading Motivation; Collection Development; New Collection